The Impact of Oil Palm Plantation Management on Soil Fertility Dynamics - Ikhsanul Adli; Aprisal; Jabang Nurdin (Jurnal Niara, 2025)
The palm oil industry is the largest economic supporter for the Indonesian economy from the agricultural sector. Behind the success story of this activity, there are environmental consequences regarding the decline in land quality as a result of improper land management. To study the effect of oil palm plantation management on soil fertility, a study was conducted in three locations, Dharmasraya Regency (Kanhapludult), South Solok (Dystrudepts) and South Coast (Haplohemists) in West Sumatra. Research data were collected from 2017 to 2022 respectively, and analyzed. The results showed that soils from Dharmasraya (DM) and South Solok (SS) experienced a decrease in pH value during the study period, while opposite results were found at the PS location. Total Carbon (C) and Nitrogen (N) content at the DM and SS locations were found to be similar, while at the PS location these parameters were much higher because the soil came from organic matter. Comparable results were also found for KTK, where the DM and SS research locations were lower compared to the PS location. The content of macro nutrients (nitrogen, phosphorus and potassium) in the soil describes the PS location much better compared to DM and SS. Because the PS location is organic soil, the higher nutrient content can be harmful to the environment because it can easily leak into water bodies which can trigger eutrophication